Makna Sosial Tentang Hidup Sehat Pada Masyarakat di Era Pandemi Covid -19 - Muhammad Nur Hidayat; Nieke Rudyanty Winanda; Endah Wahyuningsih (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Since the world entered the Covid-19 pandemic, society has experienced many changes in the new adaptations that are taking place. One of them is active in doing a healthy lifestyle. The action is caused by two motives, namely because of motive and in order to motive. This study tries to explore and analyze the social context behind individual actions in interpreting healthy living in the era of the Covid 19 pandemic by using Alfred Schutz's phenomenology approach. The selection of informants used a purposive technique with the criteria of individuals who fall into the category of productive age and work in the public sector and services dealing with the community who collect 10 informants. The results of the research in the field have 4 meanings in healthy living, namely 1) Mental health in the pandemic era, 2) family resilience as protection in the pandemic era, 3) Traditional herbal medicine as an immunity enhancer, 4) Health protocols and social distancing to prevent the spread of the Covid 19 disease.Keywords: Social Meaning; Healthy Living; Population; Productive; Covid-19 AbstrakSejak dunia memasuki masa pandemi Covid 19, masyarakat telah mengalami banyak perubahan dalam adaptasi baru yang tengah berlangsung. Salah satunya adalah tindakan dalam melakukan gaya hidup sehat. Tindakan tersebut disebabkan dua motif, yaitu motif sebab dan motif tujuan. Penelitian ini berusaha mengeksplorasi dan menganalisis konteks sosial yang melatarbelakangi tindakan individu dalam memaknai hidup sehat di era pandemi Covid 19 dengan menggunakan pendekatan fenomenologi Alfred Schutz. Pemilihan informan menggunakan teknik purposif dengan kriteria individu yang masuk dalam kategori usia produktif dan bekerja di sektor publik dan pelayanan yang berhadapan dengan masyarakat yang berjumlah 10 informan. Hasil penelitian dilapangan terdapat 4 pemaknaan dalam hidup sehat yaitu 1) Kesehatan mental di era pandemi, 2) ketahanan keluarga sebagai proteksi di era pandemi, 3) Jamu tradisional sebagai peningkat imunitas, 4) Protokol kesehatan dan social distancing untuk mencegah penyebaran virus Covid-19.Kata Kunci: Makna sosial; Hidup sehat; Penduduk; Produktif; Covid 19